Resonance frequency analysis assessment of implant stability in labial onlay grafted posterior mandibles: A pilot clinical study - (:unkn) unknown (QUINTESSENCE PUBLISHING CO INC, 2007)
Purpose: The objectives of this study were ( 1) to compare the stability, evaluated by means of resonance frequency analysis (RFA), of implants placed posterior mandibles augmented with autogenous bone harvested from the mandibular symphysis with that of implants placed in nongrafted edentulous posterior mandibles and ( 2) to compare peri-implant marginal bone height changes and implant failure for the 2 groups. Materials and Methods: Eight patients with thin posterior mandibular ridges (buccolingual crestal width less than 4 mm) underwent labial onlay alveolar grafting with symphyseal bone blocks 4 months prior to placement of 17 implants. Seven nongrafted patients received 18 implants in the edentulous posterior mandible; these patients served as a control group. RFA was performed the day of implant placement ( baseline), 1 month postplacement, 4 months postplacement ( after prosthesis delivery), and 12 months postloading. Peri-implant bone height changes at a level of 0.01 mm were assessed using periapical radiographs at baseline, the 1-month follow-up, and the 4-month follow-up. Analysis of variance was used to evaluate statistical differences within the groups, and t test was used to make comparisons between groups. Results: None of the patients presented postoperative complications or implant failure. Mean implant stability quotient (ISQ) was 63.0 +/- 6.0 to 70.2 +/- 3.5 for the grafted group and 64.1 +/- 4.1 ISQ to 70.1 +/- 3.9 for the nongrafted group. No significant difference was found in mean ISQ between the grafted and nongrafted groups at baseline, the 1-month follow-up, 4 months postplacement, or 12 months postloading ( P =.211, P =.873, P =.925, P =.735, respectively). Mean peri-implant bone loss was 0.16 +/- 0.04 mm mesially and 0.16 +/- 0.05 mm distally. Conclusion: RFA revealed no difference in implant stability between mandibular ridges augmented with autologous bone grafts at baseline or after loading.
Keywords: autogenous bone graft; edentulous posterior mandible; implant stability; resonance frequency analysis; symphysis; ALVEOLAR RIDGE AUGMENTATION; ILIAC BONE-GRAFTS; TITANIUM IMPLANTS; DELAYED PLACEMENT; ANTERIOR MAXILLA; IN-VIVO; RECONSTRUCTION; COMBINATION; RABBIT; INTERFACE